2019
DOI: 10.1175/jamc-d-18-0187.1
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Characteristics of Tornadic Vortex Signatures Associated with Long-Duration Tornadoes

Abstract: Weather Surveillance Radar–1988 Doppler (WSR-88D) data from 36 tornadic supercell cases from 2012 to 2016 are investigated to identify common tornadic vortex signature (TVS) behaviors prior to tornado dissipation. Based on the results of past case studies, four characteristics of TVSs associated with tornado dissipation were identified: weak or decreasing TVS intensity, rearward storm-relative motion of the TVS, large or increasing TVS vertical tilt, and large or increasing TVS horizontal displacement from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 77 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…In particular, the low-level mesocyclone in nontornadic storms is displaced toward the forward flank of the storm and away from the primary storm updraft (that at mid-and upper levels). This result is consistent with recent modeling work and with past observational studies that identified alignment of low-and midlevel mesocyclones with the storm updraft to be important to tornadogenesis and maintenance in supercells (e.g., Dowell and Bluestein 2002;Marquis et al 2012;Tanamachi et al 2012;French and Kingfield 2019). 3) A Z DR dipole exists at midlevels (near and in a shallow layer above the 08C isotherm) in supercells, for which its orientation relative to storm motion differs by approximately 458 between tornadic and nontornadic storms.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, the low-level mesocyclone in nontornadic storms is displaced toward the forward flank of the storm and away from the primary storm updraft (that at mid-and upper levels). This result is consistent with recent modeling work and with past observational studies that identified alignment of low-and midlevel mesocyclones with the storm updraft to be important to tornadogenesis and maintenance in supercells (e.g., Dowell and Bluestein 2002;Marquis et al 2012;Tanamachi et al 2012;French and Kingfield 2019). 3) A Z DR dipole exists at midlevels (near and in a shallow layer above the 08C isotherm) in supercells, for which its orientation relative to storm motion differs by approximately 458 between tornadic and nontornadic storms.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…The authors found that most of the obvious polarimetric signatures did not differ clearly enough for supercell type discrimination in their small sample, but noted that more extensive research was needed to better elucidate the potential utility of polarimetric observations for tornadic and nontornadic supercell discrimination. Several studies have since investigated supercell storm differences in raindrop size distributions within hook echoes (Kumjian and Ryzhkov 2008a;Kumjian 2011;French et al 2015), finding that hook echoes in tornadic supercells are often characterized by smaller raindrop distributions than nontornadic supercells, which is promising for operational storm discrimination. Another promising pattern for storm discrimination is the separation between areas of enhanced specific differential phase (K DP ) and differential radar reflectivity (Z DR ) at low ground-relative altitudes (near 1 km AGL), where the most promising signature of separation is an orientation more perpendicular to storm motion in tornadic supercells and parallel to storm motion in nontornadic supercells (Crowe et al 2012;Loeffler et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By choosing a fast forwardtranslation speed of 60 mph (26.8 m s -1 ), lower STRAKA AND KANAK 10 May 2022 9 thresholds for PD stratification can be approximated as 30, 60 and 90 min, which permits rough categorizations for short-duration PD <30 min; long-duration [30, 60) min; very long-duration [60, 90) min; and extremely longduration tornadoes PD ≥90 min tornadoes (Table 4). These can be compared to French and Kingfield (2019), who provided documentation of radar observations of 36 tornadoes with PD ≥20 min from 2012-2016, which had ranges of 20-78 min, with a median of 30 min and mean of 37 min (with uncertain representativeness). Translation speeds for the vast majority of tornadoes, parent-storm modes (supercell, QLCS, MCV) and associated mesocyclone durations in this 40-y study were unknown, and precluded a comprehensive study of tornado PD for this climatology.…”
Section: Tornado Path Length and Duration Stratificationmentioning
confidence: 99%
“…Generally, the simultaneous presence of the above-mentioned radar signatures (e.g., hook echo, MESO, TVS, WER, BWER) on radar products is considered a relevant clue for issuing tornado warnings [54]. However, previous studies have demonstrated that there is no general rule that ensures tornado occurrence based on these radar signatures [55,56]. Therefore, the warning messages issued by the Romanian meteorological service in both cases were cautious with regards to stating tornado occurrence.…”
Section: General Characteristics Of Two Convective Events Occurred In Romania In 2019mentioning
confidence: 99%